Fusoid cells in the grass family Poaceae (Poales): A developmental study reveals homologies and suggests new insights into their functional role in young leaves - Leandro, Thales D. [UNESP]; Rodrigues, Tatiane Maria [UNESP]; Clark, Lynn G.; Scatena, Vera Lucia [UNESP] (Oxford University Press (OUP), 2018)
Background and Aims In mature grass leaf blades as seen in cross-section, oblong cell-like structures have been interpreted most recently as intercellular gas spaces delimited by successive collapsed fusoid cells. These cells have been reported in at least seven of 12 subfamilies of Poaceae and are considered a synapomorphy for the family; however, no developmental work has been performed to verify their meristematic origin or to assess possible homologies within the graminid clade (= Flagellariaceae + [(Joinvilleaceae + Ecdeiocoleaceae) + Poaceae]) or among subfamilies of Poaceae. A developmental study was therefore carried out, including 20 species in three families (Flagellariaceae, Joinvilleaceae and Poaceae), representing the earlier-diverging and derived branches within the graminid clade and Poaceae. Methods Light microscopy was combined with scanning electron microscopy, cryoscanning electron microscopy and transmission electron microscopy to study the development of leaves taken from the shoot apex of young plants. Mature leaf blades also were taken from living or dried plants and the mid-portion was studied. Key Results Developmental results show that, in mature leaf blades as seen in cross-section, one apparent fusoid cell is typically a cavity resulting from the collapse of the initial fusoid cell and its internal divisions, which are herein interpreted as derivative cells with formation of cell plates only. Each cavity is delimited by successive collapsed fusoid cells arranged perpendicularly to the veins. Fusoid cells in all studied Poaceae members originate from the ground meristem, as do the colourless cells in Joinvillea ascendens (Joinvilleaceae). These two types of mesophyll cell have a strongly similar ontogeny, distinguished mainly by the collapse of the fusoid cells in Poaceae, which is not observed in the colourless cells in J. ascendens. Conclusions Within the Poaceae, the meristematic origin of fusoid cells is the same in the early-diverging lineages, BOP clade and Panicoideae, and thus they are homologous within the family. The same topography and meristematic origin suggest that fusoid cells in Poaceae and colourless cells in Joinvilleaceae are homologous. The results also suggest that the role played by the fusoid cells in young grass leaves is related to synthesis and storage of starch granules at early stages of development.
Keywords: BOP clade; early-diverging grass lineages; Flagellariaceae; foliar anatomy; graminid clade; grasses; Joinvilleaceae; mesophyll cells; ontogeny; Panicoideae